The correlations of serum uric acid with lean mass, fat mass and grip strength in adolescents aged 12-19 years - Xu, Feng; Shen, Jianjun; Zhu, Zhongxin (Frontiers in Endocrinology, 2025)
BackgroundSerum uric acid (sUA) has emerged as an intriguing modulator of body composition and physical function, yet its complex associations with musculoskeletal parameters during the critical period of adolescence remain incompletely characterized. To address this knowledge gap, we sought to elucidate the relationships between sUA and key indicators of body composition and musculoskeletal health in adolescents aged 12-19 years, specifically examining appendicular lean mass index (ALMI), appendicular fat mass index (AFMI), and combined grip strength.MethodsIn this cross-sectional study, we analyzed data from 2,003 adolescents participating in the National Health and Nutrition Examination Survey (NHANES) 2011-2014. We examined the relationships between sUA and ALMI, AFMI, and combined grip strength using multivariate linear regression models. Subgroup analyses were conducted to explore effect modifications by age, sex, and race/ethnicity.ResultsHigher sUA levels were positively associated with ALMI and grip strength, and inversely associated with AFMI after adjusting for potential confounders. These associations exhibited distinct patterns across age, sex, and race subgroups, with the most pronounced effects observed among boys aged 12-15 years and in non-Hispanic White and Black populations.ConclusionsOur findings demonstrated significant associations between sUA levels and various parameters of musculoskeletal health and body composition, suggesting that sUA may serve as a potential biomarker for monitoring physical development and maturation during adolescence.